Lifetime Impact of Cow’s Milk on Overactivation of mTORC1: From Fetal to Childhood Overgrowth, Acne, Diabetes, Cancers, and Neurodegeneration - Melnik, Bodo C. (Biomolecules, 2021)
The consumption of cow’s milk is a part of the basic nutritional habits of Western industrialized countries. Recent epidemiological studies associate the intake of cow’s milk with an increased risk of diseases, which are associated with overactivated mechanistic target of rapamycin complex 1 (mTORC1) signaling. This review presents current epidemiological and translational evidence linking milk consumption to the regulation of mTORC1, the master-switch for eukaryotic cell growth. Epidemiological studies confirm a correlation between cow’s milk consumption and birthweight, body mass index, onset of menarche, linear growth during childhood, acne vulgaris, type 2 diabetes mellitus, prostate cancer, breast cancer, hepatocellular carcinoma, diffuse large B-cell lymphoma, neurodegenerative diseases, and all-cause mortality. Thus, long-term persistent consumption of cow’s milk increases the risk of mTORC1-driven diseases of civilization. Milk is a highly conserved, lactation genome-controlled signaling system that functions as a maternal-neonatal relay for optimized species-specific activation of mTORC1, the nexus for regulation of eukaryotic cell growth, and control of autophagy. A deeper understanding of milk´s impact on mTORC1 signaling is of critical importance for the prevention of common diseases of civilization.